Leadership: A new perspective - Elwell, Elizabeth A; Malik, Leela (New Delhi R and K Publication., 1974)
Currently there are three views of leadership . These three views are popularly known as the traitist view , the groupist view , and the situationist view . Scholars accept that each of these views identify significant leadership factors but fail , singly or in combination , to capture the complex phenomenon of leadership . The three views of leadership arise from the perspective of leadership as a leader - follower relation . The purpose of this book is to present an alternative perspective that includes these views and the leadership factors they identify as well as new views and new factors that arise out of an in - depth analysis of this complex and elusive phenomenon . The new perspective of This new leadership presented in this book regards leadership systems as ensembles of two primary and complex elements . perspective is developed as an analytical theoretical system . the hope that it will serve to ( 1 ) This book is presented sensitize us to the complex of possible constraints upon and functional channels of leadership ; ( 2 ) guide us in the organi zation of leadership systems for given purposive acts ; and ( 3 ) stimulate further research on leadership . The book opens with an introduction to theory - building and a review of leadership research studies . Part one is devoted to the generation of a model of leadership as an adaptive action system . Part two presents the model of leadership as an adaptive action system and dis cusses its syntax and semantics . Parts one and two represent an application of the techniques involved in the development of analytical theoretical systems . The book concludes with a succinct statement of the perspective of leadership as an adaptive action system . Struggling with a new idea , attempting to organize and com municate a new idea - such is the excitement , fascination , challenge , and frustration of theoretical research . It is hopedvi that the exposé of theory - building presented in this book will serve to stimulate further study of theory - building and be of some assistance to researchers attempting to develop analytical theoretical systems .
Keywords: Leadership